2014
DOI: 10.1186/1478-4505-12-48
|View full text |Cite
|
Sign up to set email alerts
|

Systematic reviews addressing identified health policy priorities in Eastern Mediterranean countries: a situational analysis

Abstract: BackgroundSystematic reviews can offer policymakers and stakeholders concise, transparent, and relevant evidence pertaining to pressing policy priorities to help inform the decision-making process. The production and the use of systematic reviews are specifically limited in the Eastern Mediterranean region. The extent to which published systematic reviews address policy priorities in the region is still unknown. This situational analysis exercise aims at assessing the extent to which published systematic revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 18 publications
3
7
0
Order By: Relevance
“…The majority of included systematic reviews were conducted by authors affiliated with institutions in high income countries, a finding consistent with the small proportion of systematic reviews from low and middle income countries in general. 24 - 27 We also found that the majority of systematic reviews address the delivery arrangements topic, which corroborates the findings of previous studies on the topics covered by HPSR systematic reviews. 24 - 26 …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The majority of included systematic reviews were conducted by authors affiliated with institutions in high income countries, a finding consistent with the small proportion of systematic reviews from low and middle income countries in general. 24 - 27 We also found that the majority of systematic reviews address the delivery arrangements topic, which corroborates the findings of previous studies on the topics covered by HPSR systematic reviews. 24 - 26 …”
Section: Discussionsupporting
confidence: 90%
“… 24 - 27 We also found that the majority of systematic reviews address the delivery arrangements topic, which corroborates the findings of previous studies on the topics covered by HPSR systematic reviews. 24 - 26 …”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, a stocktaking exercise on HPSR production gaps in 12 EMR countries revealed significant inconsistencies between HPSR produced and regional HPSR priorities, emphasizing the need for more HPSR and its alignment with the demand for evidence by policymakers [ 15 ]. Additionally, a regional situational analysis exercise showed major gaps in the production of systematic reviews to address identified health policy priorities [ 16 ]. The limited number and scope of publicly accessible data was also shown to hinder the ability to employ evidence-informed decisions [ 17 ].…”
Section: Contextmentioning
confidence: 99%
“…Using this tool is particularly relevant in the context of low- and middle-income countries, where the capacity of production of systematic reviews is limited and often misaligned with policy needs and priorities [ 11 , 27 , 28 ]. The prioritisation can help channel limited resources to areas of highest priority [ 27 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Groups or institutions funding or conducting systematic reviews in HPSR should prioritise topics according to the needs of policymakers and stakeholders [ 11 , 12 ]. A prioritisation process can increase the likelihood that the best available evidence informs health policy decision-making [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%